Estimation of path coefficient analysis to identify the yield contributing traits in rice (Oryza sativa L.) under saline and non-saline coastal regions of West Bengal - KUNDU, SRITAMA; Kundagrami, Sabyasachi (JOURNAL OF ADVANCES IN BIOLOGY, 2015)
The study was conducted out for three consecutive years (2009, 2010, and 2011) at Baruipur, a non-saline zone. Parallel field trials were conducted at Sagardeep, a saline zone in 24Pgns, south in 2009 and 2010 and at Hingalganj (24Pgns, North) another saline prone zone in 2011. At maturity plants were harvested taking five randomly selected plants from each replication and eight different agro-morphological characters namely plant height, tillers per hill, panicles per plant, grains per panicle, panicle length, 1000 seed weight, seed yield per plant and days to maturity were recorded. The objectives were to determine traits affecting grain yield in forty three paddy genotypes and to establish the nature of relation between grain yield and yield components. In the path coefficient analysis, it was observed that the direct effects on seed yield per plant were exhibited by grains per panicle, tillers per hill, and days to maturity. On the other hand, the indirect effects of grains per panicle through other traits also indicated that direct selection using grains per panicle to select high yielding genotypes will be effective.